Unity 2017 Game AI Programming : leverage the power of Artificial Intelligence to program smart entities for your games /: leverage the power of Artificial Intelligence to program smart entities for your games. ([2018]) - Barrera, Ray; Kyaw, Aung Sithu; Swe, Thet Naing
No abstract available